Comparative analysis of onabotulinum toxin type-A injection techniques in older adults with blepharospasm: a retrospective cohort study - Poyraz, Turan; Çilengiroğlu, Özgül Vupa (Frontiers in Neurology, 2025)
IntroductionBenign essential blepharospasm (BEB) is a focal dystonia that can lead to functional blindness in older adults. While botulinum neurotoxin (BoNT) is widely utilized in the treatment of BEB, there remains a lack of consensus regarding the optimal injection technique. This study aims to compare the clinical outcomes and measurable scales associated with injections into the orbicularis oculi muscle at the pars pretarsalis (PPT) and pars preseptalis (PPS) regions, assessing their efficacy and side effects.MethodsThe study included 32 patients diagnosed with BEB. Two injection techniques utilizing onabotulinum toxin type-A—PPT and PPS—were compared. The modified Jankovic Scale (mJS) was used to assess the clinical severity and frequency of blepharospasm. At the same time, the Blepharospasm Disability Scale evaluated the associated disabilities. The Schirmer I test was used to assess dry eye symptoms post-BoNT administration. Adverse effects were self-reported, and participants were examined at 1- and 3-month follow-up.ResultsBoth injection techniques resulted in significant improvements in the mJS severity and frequency scores, as well as the Blepharospasm Disability Scale (p < 0.05). Notably, improvements in ocular dryness were particularly pronounced at the 1-month mark (p < 0.05). The PPT injection technique displayed a superior safety profile, with the total number of adverse events statistically greater in the PPS group compared to the PPT group (p < 0.05).ConclusionBoNT injections through both PPT and PPS techniques are effective in treating BEB in older adults. However, the PPT technique demonstrates a lower incidence of adverse events, rendering it a preferable choice for clinicians managing BEB.